An Improvement on Exploration Step of Whale Optimization Algorithm with Levy Distribution for Classification Problems - Sakkayaphop Pravesjit; Krittika Kantawong; Natdanai Kamkhad; Saksit Sabaiporn; Jantawan Monchanuan; Duangjai Jitkongchuen; Arit Thammano; Panchit Longpradit (My University, 2024)
The proposed system represents an enhanced movement in search of food of Whale Optimization Algorithm (WOA), based on Levy distribution for image classification of grape leaf disease. In the preprocessing, the proposed system uses convolution kernels to transform images into input data within the range of (0,1). Thereafter, the Levy distribution is incorporated into the WOA model as an exploration search mechanism. A grape leaf dataset from the Plant Village project (www.plantvillage.org), consisting of 4062 labeled images with dimensions of 256 by 256 pixels and divided into four classes -healthy, Black Rot, Black Measles, and Isariopsis leaf spot -is used to evaluate the performance of the proposed system. Experimental results show that the proposed system is better than Visual Geometry Group (VGG16), Gray Level Co-occurrence Matrix (GLCM) with SVM, Low contrast haze reduction-neighborhood component analysis with SVM, and whale optimization algorithm (WOA).
Keywords: Advanced Algorithms and Applications; Advanced Sensor and Control Systems